Environmental health engineering in the tropics: An introduction text - Sandy Cairncross (John Wiley, 1993)
This book is concerned with policy nad trategies for implementing water and sanitation programmes. This book contains a distillation of much knowledge and experience and many people have contributed to it in various ways